Does the way I see you affect the way I see myself? Associations between interviewers' and interviewees' "color/race" in southern Brazil - João Luiz Bastos; Samuel Carvalho Dumith; Ricardo Ventura Santos; Aluísio J. D. Barros; Giovâni Firpo Del Duca; Helen Gonçalves; Ana Paula Nunes
This study assessed the associations between female interviewers' self-classified "color/race" and participants' self- and interviewer-classified "color/race". A cross-sectional study was carried out among adult individuals living in Pelotas, southern Brazil. Associations were examined by means of contingency tables and multinomial regression models, adjusting for interviewees' socioeconomic and demographic factors. Individuals aged > 40 years were 2.1 times more likely to classify themselves as brown (versus white) when interviewed by black (as compared to white) interviewers. Participants in the same age group were 2.5 times less likely to classify themselves as black (versus white), when interviewed by black interviewers. These differences were even greater among men 40 years or older. Compared to white interviewers, black female interviewers were 2.5 times less likely to classify men aged > 40 years as black. These results highlight the complexity of racial classification, indicating the influence of the interviewer's physical characteristics on the interviewee's "color/race".